Performance of photovoltaic pumping station using a centrifugal motor-pump working at fixed speed - Simonguy, Eric; Korsaga, Eric; Mâ€™boliguipa, Jean; Tilado GuinganÃ©, Toussaint; Koalaga, Zacharie (International Journal of Engineering and Technology, 2019)
The work presented in this paper studies the performances of a direct coupled photovoltaic (PV) pumping system such as the water storage is carried out indirectly in a tank. The centrifugal pump is driven by a squirrel cage Asynchronous Motor (AM) fed by three-phase voltage inverter using a Pulse Width Modulation (PWM) swictching technique. The strategy of Boost converter command by Proportional-Integral (PI) controller is used to feed the motor-pump with constants voltage and frequency. The simulation results in Matlab/Simulink software show that, on the one hand, the dynamic performances of the motor pump depend of the rotor inertia moment (or mechanic power) and on the other hand, the evolution of the water volume is not affected by the rapid variations of illumination.Â